Thematic Animal Postage Stamps of Malaysia: Study of State Narratives from the Colonialism to the Post-Colonialism - Kay, Shin Yan (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2020)
This research explores the visual representation of animals in postage stamps issued in North Borneo, Sarawak, British Malaya and Malaysia from the 19th to the 20th century. Since postage stamps were an official product of the State, this research exemplifies the postage stamp as a part of the visual culture that facilitates different State narratives and reveals their contribution towards the formation of colonial or national identities. Furthermore, the study explores visual art from a sociocultural perspective, intending to augment its value as a piece of historical evidence. It shows the visual representations of postage stamps as a record of the civilising process by examining the changes in animal representation as it shifts from a kaleidoscope of exotic romanticism towards the righteous pride of animal protection in the postcolonial era. More than hundreds of thematic animal stamps that were issued in Malaysia were examined in order to identify the preferences influencing animal selection in both colonial and postcolonial era. Following that, background studies, theoretical analysis and visual methodologies form the main research approaches. This paper addresses the research gap that State narratives are disputable without any visual cultural element or ideological construct.